2010
DOI: 10.1016/j.carbpol.2010.05.031
|View full text |Cite
|
Sign up to set email alerts
|

Caesalpinia ferrea var. ferrea seeds as a new source of partially substituted galactomannan

Abstract: a b s t r a c tThe hydrocolloid extracted from Caesalpinia ferrea var. ferrea seeds purified by membrane filtration was denominated GMPF (14% yield) and contained 75% total carbohydrate and 9% protein, and the mannose to galactose (Man:Gal) ratio was around to 2.1:1.0. The periodate oxidation, methylation and 1D/2D NMR spectra results indicated galactomannan (GM) with a (1 → 4)-linked ␤-d-mannopyranose backbone, partially substituted at O-6 with single-unit ␣-d-galactopyranose side-chains. The splitting of thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 40 publications
0
3
0
4
Order By: Relevance
“…The 1D/2D NMR Nakamura et al, 2002a,b;Vasconcelos et al, 2011;Silva et al, 2013;Silva et al, 2014;Port´s et al, 2013;Araújo et al, 2014 Methyl spectra indicated the presence of galactomannan with a (1→4)-linked-β-D-mannopyranose, partially substituted at O-6 with single-unit α-D-galactopyranose side-chains. The splitting of three 13 C signals in the region of the 4-O-Manpyranose units revealed the α-D-Galpyranose units (Souza et al, 2010). Another study showed the presence of polysaccharides in aqueous extract from the seeds following sulfation.…”
Section: Polysaccharidesmentioning
confidence: 96%
“…The 1D/2D NMR Nakamura et al, 2002a,b;Vasconcelos et al, 2011;Silva et al, 2013;Silva et al, 2014;Port´s et al, 2013;Araújo et al, 2014 Methyl spectra indicated the presence of galactomannan with a (1→4)-linked-β-D-mannopyranose, partially substituted at O-6 with single-unit α-D-galactopyranose side-chains. The splitting of three 13 C signals in the region of the 4-O-Manpyranose units revealed the α-D-Galpyranose units (Souza et al, 2010). Another study showed the presence of polysaccharides in aqueous extract from the seeds following sulfation.…”
Section: Polysaccharidesmentioning
confidence: 96%
“…On the 13 C spectrum, the relative areas of the signals of the anomeric carbons at d 100.5 and d 99.3 (galactose and mannose, respectively) resulted in a G/M ratio of 1.00:1.08. The signals of H2/C2 (3.8/69.03 ppm), H3/C3 (3.83/70.05 ppm), H4/C4 (3.9/71.7 ppm), and H5/C5 (3.89/ 71.7 ppm) correspond to a-D-galactopyranosyl, whereas those of (Pires, Gorin, Reicher, & Sierakowski, 2001), whereas the signal at 67.1 ppm was assigned to C-6 of b-D-mannopyranosyl substituted by the a-D-galactopyranosyl unit (Albuquerque et al, 2014;Pires et al, 2001;Souza et al, 2010).…”
Section: Msg Characterizationmentioning
confidence: 99%
“…O sorvete oferece uma combinação de propriedades sensoriais altamente desejáveis, sendo estas classificadas em atributos como o de aparência, cor, maciez, regularidade, aroma, sabor e textura/preenchimento bucal (dureza, viscosidade, cremosidade) (SOUZA et al, 2010).…”
Section: Variáveis Analisadasunclassified
“…Galactomananas utilizadas em sorvetes nas concentrações entre 0,2 e 0,5%, possuem grande capacidade de retardar o crescimento de cristais de gelo (SOUZA et al, 2010;VARELA;PINTOR;FISZMAN, 2014). Além disso, os estabilizantes também contribuem para a melhoria da textura, características de fusão e sabor do sorvete (PATMORE; GOFF; FERNANDES, 2003; SOUKOULIS; LEBESI; TZIA, 2009).…”
Section: Introductionunclassified
See 1 more Smart Citation